Supply Chain Perfomance in Expedition Services Using The Supply Chain Operations Reference (SCOR) and Analytical Hierarchy Process (AHP) Methods - Widyarto, Wahyu Oktri; Shofa, Mohamad Jihan; Wiliyanto, Reza (Jurnal Logistik Indonesia, 2025)
The internet continues to evolve alongside the rapid advancements in information technology, which is one of the characteristics of the Fourth Industrial Revolution (Industry 4.0) that influences the transformation of business processes from conventional methods to e-commerce. Expedition services are a key player in the Supply Chain Management (SCM) process, making a significant contribution to e-commerce as providers of goods delivery services. Currently, the expedition service industry is growing rapidly, largely driven by the expansion of online business or e-commerce. This paper discusses the supply chain (SC) performance in the expedition service sector, considering that the topic of SC performance in this sector still requires further development. The research uses the SCOR model to measure SC performance based on five key processes: plan, source, deliver, return, and enable. Performance indicator weighting is conducted using the AHP method. Based on the data analysis, it was found that the SC performance value is 82.53%, which falls within the "average" category. The highest weight was found in the "deliver" performance metric at 50.44%, while the lowest performance value was observed in the "enable" metric at 6.33%.